Trabalho e aposentadoria: motivações da permanência no trabalho entre profissionais de enfermagem de nível médio - Alberici, Clotilde (2016)
The aim of this study is to investigate between mid-level nursing professionals and federal civil servants. In specific, what the motivations of staying at work are when they met all the prerequisites for retirement with full pay. The analysis of the stories shared, the feeling of belonging, the built ties, the roles played within the institution and outside it, and the meaning of work and retirement were guiding categories founded by González Rey and by the perspective of historical-cultural psychology. Three mid-level nursing professionals were interviewed. They used the qualitative methodology of exploration through semi-structured interviews that were analyzed through Meaning Centers. It is viewed that the the main motivation for staying at work is the sense of belonging and mutual trust established in the work combined with the absence of such strong links in the family and in society. The significance of care, built on the subjectivity of one interviewee, can also be cited as motivation for his stay at work. Retirement in this context is generating anxiety, since it means a break with the world of work, and it is this that gives meaning to their lives. These findings indicate the importance of thinking about preparation programs for Retirement that are able to bring the subject to produce new meanings to their lives, reflect on the meaning of work and retirement with professionals, generating new areas of interest and new meanings over working life. It is suggested to further research in the area of health and psychology, the meaning of work, the working hours on weekends and its implications in subjectivity in the construction of forms of sociability of professionals